Design concept of horse arena in Malaysia – A case study - Nur Fadilah, Darmansah; Sitti Diana, Tamjehi; Abdul Wafi, Razali; Nadia, Zaini; Sharifah NurFarhana, Syed Sahimi (IOP Publishing, 2019)
One of the most important facilities required for any equine centre is horse arena. Horse arena is a place where horse doing the execrsice. Its a dedicated riding space is useful for training purposes. Equine Center may include an outdoor arena, indoor arena, or both. This paper presents the findings from a case study on the arena design concept throughout Malaysia. A total of fourtytwo (42) Equine Centre throughout the country were selected and visited in the study. The items studied include the types of arena, size of arena, material used for surface and fencing. The results indicated that about 79% of the arena used outdoor design, 31% of the arena had arena size of 20m x 60m ,56% used Polyvinyl Chloride (PVC) as the main material of fencing, and almost 74% used sand as types of surface in arena. Then for the indoor arena, the design concept of the roof structure was 79% used gable type of design with 81% used zinc as the roofing material. Generally, it can be said that the design concept of the horse arena in Malaysia depends on the owner needs, activities of the equine centre whether it is use for training or game.